Autocatalytic oncotherapy nanosystem with glucose depletion for the cascade amplification of hypoxia-activated chemotherapy and H2O2-dependent chemodynamic therapy. (6th April 2022) - Hu, Yao; Bai, Song; Fan, Xingyu; Zhou, Fangfang; Chen, Botao; Tan, Songwen; Xu, Hui; Pan, Anqiang; Liang, Shuquan; He, Yongju
Abstract : An autocatalytic nanosystem with glucose depletion for triple synergetic cancer starvation therapy, cascade amplified hypoxia-activated chemotherapy and enhanced H2 O2 -dependent chemodynamic therapy. Abstract : Employing hypoxia-activated prodrugs is an appealing oncotherapy strategy, but limited by insufficient tumor hypoxia. Moreover, a standalone prodrug fails to treat tumors satisfactorily due to tumor complexity. Herein, a nanosystem (TPZ@FeMSN-GOX) was established for triple synergetic cancer starvation therapy, hypoxia-activated chemotherapy and chemodynamic therapy (CDT). TPZ@FeMSN-GOX was prepared by synthesizing iron-doped mesoporous silica nanoparticles (FeMSNs) followed by surface conjugation with glucose oxidase (GOX), and then loading with hypoxia-activated prodrug tirapazamine (TPZ). When TPZ@FeMSN-GOX entered the tumor cells, GOX could not only exhaust glucose to starve cancer cells and concomitantly produce H2 O2, but also consume O2 to aggravate the hypoxia environment and amplify TPZ-mediated chemotherapy. Meanwhile, the released Fe 3+ was reduced to reactive Fe 2+ by endogenous glutathione, which ultimately decomposed the produced H2 O2 and endogenous H2 O2 into highly toxic ˙OH, guaranteeing highly efficient CDT. Together, TPZ@FeMSN-GOX could effectively kill cancer cells and significantly inhibit tumor growth, providing a good paradigm for effective tumor treatment.